2019
DOI: 10.1016/j.ajhg.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl-tRNA Synthetase Mutations Cause a Multi-System, Recessive Disease That Includes Microcephaly, Developmental Delay, and Brittle Hair and Nails

Abstract: Aminoacyl-tRNA synthetases (ARSs) are essential enzymes responsible for charging tRNA molecules with cognate amino acids. Consistent with the essential function and ubiquitous expression of ARSs, mutations in 32 of the 37 ARS-encoding loci cause severe, early-onset recessive phenotypes. Previous genetic and functional data suggest a loss-of-function mechanism; however, our understanding of the allelic and locus heterogeneity of ARS-related disease is incomplete. Cysteinyl-tRNA synthetase (CARS) encodes the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 58 publications
4
29
0
Order By: Relevance
“…Among these, we identify tRNA regulation as one of the most significantly restored pathways in the absence of p19 Arf . Importantly, p19 Arf can directly block tRNA synthesis (27), while disruption of tRNA function is strongly associated with microcephaly and neurodevelopmental disorders (26,(28)(29)(30)(31)(32). Together, our findings support that VPA induction of p19 Arf -mediated senescence causes a broad repression of key developmental pathways, including tRNA function, thereby disrupting early neurodevelopmental steps.…”
Section: Discussionsupporting
confidence: 60%
“…Among these, we identify tRNA regulation as one of the most significantly restored pathways in the absence of p19 Arf . Importantly, p19 Arf can directly block tRNA synthesis (27), while disruption of tRNA function is strongly associated with microcephaly and neurodevelopmental disorders (26,(28)(29)(30)(31)(32). Together, our findings support that VPA induction of p19 Arf -mediated senescence causes a broad repression of key developmental pathways, including tRNA function, thereby disrupting early neurodevelopmental steps.…”
Section: Discussionsupporting
confidence: 60%
“…We here extend this classification, and highlight a possible contribution of protein translation disturbances in the pathophysiology of TTD. Recently, mutations in aminoacyl-tRNA synthetases were identified to cause TTD (Kuo et al, 2019, Theil et al, 2019) implying that a disturbed translation process, as shown in this study, might be causal for the developmental delay and neurodegeneration observed in TTD. This assumption is based on the hypothesis that only disturbances in a common cellular signaling pathway that is affected by all genes in this genotypical heterogenous disease can explain the phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…More than 60 disorders are associated with mutations in ARS genes and, depending on their individual genotype, follow both dominant or recessive inheritance patterns. [4][5][6][7][8][9][10] Cytosolic phenylalanyl-tRNA synthetase (FARS1) ranks among the most complex of the ARSs with a hetero-tetrameric structure, consisting of two FARS alpha (FARSA) and two FARS beta (FARSB) subunits. 11 The hypothesis that both genes may be associated with a similar multisystemic human disease, including features of interstitial lung disease, liver disease, neurological manifestations, and growth restriction (MIM: 619013, 613 658), needs further support.…”
Section: Introductionmentioning
confidence: 99%